Blended Learning for Chassis Maintenance and Light Vehicle Power Transfer Subject - Oktovianus Nau Lalian; Eveline Siregar; Murni Winarsih (Universitas Pendidikan Ganesha, 2020)
The aimed of this study was to develop blended learning for Chassis Maintenance and Light Vehicle Power Transfer subject for second-grade students of light vehicle engineering major at Dewantara vocational school which is expected to help students and teacher in the learning process as a learning strategy to overcome the problem of lack of face-to-face time in class. The procedure for developing blended learning used the ADDIE model which is integrated with PEDATI at the instructional design stage. Data collection techniques are done by observation, interviews, and questionnaires. Data analysis techniques used qualitative and quantitative descriptive data analysis. Based on the results of the feasibility analysis from the material expert, the percentage of achievement level is 91.67% with a very good qualifications and appropriate to be used with revisions as needed, based on the results of the feasibility analysis from media expert, the percentage of achievement level is 80% with a good qualifications, and feasible to be used with revisions as needed, and based on the results of the feasibility analysis from the instructional design expert the percentage of achievement level is 96.47% with a very good qualifications, and feasible to use without any revisions. The development of blended learning will be very effective for the achievement of learning objectives optimally and efficiency in the use of learning time in class. This result implies that the blended learning is feasible to facilitate learning especially in limited learning time at school.